Ovarian tissue cryopreservation for a girl with combined severe hemolytic anemia due to pyruvate kinase deficiency: a case report and literature review - Lingling Jiang; Xiangyan Ruan; Juan Du; Jiaojiao Cheng; Yanglu Li; Muqing Gu; Yanqiu Li; Fengyu Jin; Jinshan Zhang; Jianji Xu; Alfred O. Mueck (Gynecological Endocrinology)
Objective To present a young girl with pyruvate kinase deficiency (PKD) and concurrent severe hemolytic anemia who underwent fertility preservation and cryopreservation. Clinical symptoms, diagnosis, treatment, and new strategies for fertility protection and preservation in PKD patients who require allogeneic hematopoietic stem cell therapy are explored.Case presentation Six-year-old girl with persistent unconjugated hyperbilirubinemia and severe hemolytic anemia since birth, continuous elevation of bilirubin levels and severe splenomegaly. She was diagnosed with PKD, an open laparotomy for splenectomy was performed and ovarian tissue cryopreservation (OTC) was used to preserve fertility and ovarian endocrine function. Due to the previous donor being unsuitable, it took five months to find and match a new hematopoietic stem cell donor. Five months after OTC, the patient underwent high-dose busulfan and ciclosporin chemotherapy in preparation for peripheral blood stem cell transplantation and received rabbit anti-T-lymphocyte globulin to prevent graft-versus-host disease. Her red and white blood cells, hemoglobin and platelets are now generally within the normal range, total bilirubin and direct bilirubin in liver function have also normalized and AMH is below the lower limit of normal. Until now, no signs of a negative impact of OTC have been observed.Conclusion Hematopoietic stem cell transplantation is essential for effective treatment of pyruvate kinase deficiency. We assess OTC as the only possible fertility preservation method for children who cannot undergo embryo and oocyte cryopreservation.